ANALISIS UNSUR-UNSUR INTRINSIK CERPEN “SENYUM KARYAMIN” KARYA AHMAD TOHARI - Dewi Nurcahyati; Ai Yulianti; Dede Abdurrokhman (IKIP Siliwangi, 2019)
This study examines the intrinsic elements of the short story entitled